Population, Land Use and Livestock Composition in India and its Arid Zone - Malhotra, S P; Rao, J S; Goyal, D; Patwa, F C (Annals of Arid Zone, 2016)
The hot Indian arid zone covers 10 per cent of the total surface area of the country, is inhabited by about 19 million people and about 23 million domestic animals. The analysis of data pertaining to population characteristics, land use, crops grown, livestock kept etc. in the country and its arid zone reveal that there are regional imbalances and the situation on many scores in Indian arid zone is much worse. The growth rate of population in the Indian arid zone is comparatively much higher, (26.04% during a decade as against 24.66 per cent for the entire country) literacy rate and leval comparatively much lower (22.7% as compared to 29.3% for the entire country) and a greater concentration of workers on the occupation of cultivation (72.14 per cent in arid zone as compared 68.63% in the country as a whole). The area under forests is very meagre. More than 25 percent of the waste lands of the country are located in the hot Indian arid zone. The crops grown in the Indian arid zone are mostly rainfed crops, the percentage of double cropped area being only 3.65 as compared to about 15 per cent of such area in the country. Though it occupies one-tenths of the country’s area, the Indian arid zone contributed only 2.40 per cent of the cereals produced in the country. The percentage contribution to total production of Bajra and cotton (21.2 and 34.28 per cent respectively of the whole country) had, however, been quite substantial from the Indian arid zone. Wherever irrigation .facilities are available the per hectare average yield of wheat, barley, maize. and cotton crops had been higher for Population Land Use t 117 the arid areas. The livestock population in the Indian arid zone constitutes 6.66 per cent of the total livestock in the country. Sheep, goat and camels constitute comparatively higher percentage. The total livestock population exceeds human population and the density of livestock on the cultivated lands, on permanent pastures and grazing lands and per unit of human population is comparatively higher in Indian arid zone.